Visual Communication of Climate Change in Online Lithuanian Media - Pelikšienė, Rūta (Information & Media, 2025)
Climate change has multiple long-term and diverse effects but is usually not experienced directly. Therefore, the role of the media is particularly important to understand climate change. It is possible to communicate not only with text, but also with images, which can provide an additional dimension of perception to the analyzed phenomenon. Visualization can help the audience understand complex phenomena, especially related to the topic of climate change. This article presents an analysis of visual communication of climate change in online Lithuanian media. The analysis uses the database of online media collected during the project “Public Perceptions of Climate Change: Lithuanian Case in a European Comparative Perspective”. Based on the selected criteria, 78 illustrations from 49 articles in which climate change is the main topic were included in the analysis. The selected visualizations were analyzed thematically; as also, the concreteness and abstractness level, based on the construal level theory, was explored. The results of the study reveal the general trends in visual climate change communication in popular Lithuanian online media, the recurring themes, and the orientation towards the depiction of the effects of climate change rather than solutions. This study can be considered an initial step towards a deeper understanding of visual communication of climate change.